An Analysis of Online Learning Method Design for Theological Education in the Digital Age: A Systematic Literature Review Approach - Saputro, Anon Dwi; Wijaya, Hengki (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to analyse the development and design of an online curriculum for theological education in the digital era through a Systematic Literature Review (SLR) approach. Data was collected using Publish or Perish 8 software from Google Scholar, with the keywords “theological education in the digital era” and “online curriculum design” within the publication range of 2014 to 2024. From the initial 200 pieces of literature identified, a rigorous screening process was conducted based on title, abstract, and keywords, resulting in 23 relevant articles. Next, a thorough analysis of the full content of the articles was conducted based on predetermined inclusion and exclusion criteria, resulting in the selection of 11 articles suitable for further study. The results revealed various trends, challenges, and strategies in the development of online curriculum for theological education, including the integration of digital pedagogy, contextual theological frameworks, and learner-centred learning models. This study provides an integrated understanding of how theological education institutions are responding to digital transformation and provides a basis for future curriculum innovation.